1970
DOI: 10.3329/bjm.v23i2.875
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Serotype Distribution of <i>Campylobacter jejuni</i> and <i>Campylobacter coli</i> Isolated from Diarrhoeic Patients in Dhaka, Bangladesh, and Cape Town, South Africa

Abstract: Clinical characteristics and serotype distribution of Campylobacter jejuni and Campylobacter coli isolated from paediatric diarrhoeic patients over a three-year period in two geographically diverse areas, Dhaka, Bangladesh, and Cape Town, South Africa, were compared. Both Dhaka and Cape Town patients had similar rates of diarrhoea, vomiting and fever. However, the Dhaka patients were younger (11.8 vs. 13.0 months), had more boys than girls infected (male/female ratio 1.78:1 vs. 1.25:1), had more predisposing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…curvus and C . sputorum because these species presented the lowest prevalence (0.02% for both) and were tested in the same study from South Africa [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…curvus and C . sputorum because these species presented the lowest prevalence (0.02% for both) and were tested in the same study from South Africa [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies in Bangladesh reported a variable level of prevalence rate during the 1990s ranging from 17 to 26% with C. jejuni [19,20] and 9.45% with C. jejuni and 2.68% with C. coli spanning from 2005 to 2008 [21]. A few separate studies confirmed 8.5% prevalence for Campylobacter jejuni and Campylobacter coli in fecal specimens [22] and 15.3% and 11.3% prevalence of Campylobacter jejuni and Campylobacter coli, respectively [23]. However, a most recent study confirmed the prevalence of C. jejuni/coli as 28.3% in 2019 [24].…”
Section: Introductionmentioning
confidence: 92%
“…Human illnesses are dominantly associated with C. jejuni, however, other Campylobacter species of clinical significance are emerging [5]. Differences identified in clinical presentation and serotype distribution indicate that reservoirs and patterns of illness differ at both the local and regional scale [6]. Risk factors for contracting campylobacterosis in developing countries are associated with environmental exposures, including animal contact, contaminated food, source of drinking water, and sanitation access [7,8].…”
Section: Introductionmentioning
confidence: 99%